Gambaran Kesesuaian Alat Kerja dengan Antropometri Pegawai Dinas Kesehatan Kabupaten Belu - Elisabeth Y. Manek; Agus Setyobudi; Mustakim Sahdan (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
How well the ergonomic work tool fits the human size determines how comfortable and uncomfortable it is to use it. Determining the suitability of the work tool with the anthropometry of the employees of the Belu District Health Office is the purpose of this study. Descriptive methods combined with quantitative approaches are used in this kind of research. 30 participants are the population and sample used in this study, which includes seven types of chairs and all sampling techniques. The findings of the study showed that, among the staff of the Belu District Health Office, 12 (40%) were male and 18 (60%) were female in terms of anthropometric measurements. The dimensions of the 7 types of chairs used by male employees are categorized as appropriate because the height of the chair legs with the height of the employee's knees are included in the anthropometric measurements. While for female employees, the appropriate one is a computer chair because the height of the chair legs can be adjusted according to the needs of female employees in anthropometric measurements. The most common type of complaint is in the mild category with 17 people (56.7%), the moderate category with 12 people (40%), and the severe category with 1 person (3.3%).